Effect of Pressure, Reconstituted RTE Meat Microbiota, and Antimicrobials on Survival and Post-pressure Growth of Listeria monocytogenes on Ham - Teixeira, Januana S.; Repková, Lenka; Gänzle, Michael G.; McMullen, Lynn M. (Frontiers in Microbiology, 2018)
Pressure treatment of ready-to-eat (RTE) meats extends the shelf life and reduces risks associated with Listeria monocytogenes. However, pressure reduces numbers of Listeria on ham by less than 5 log (CFU/g) and pressure effects on other meat microbiota are poorly documented. This study investigated the impact of pressure and RTE meat microbiota, with or without nisin and rosemary oil, on survival of Listeria after refrigerated storage. Ham was inoculated with a 5-strain cocktail of L. monocytogenes alone or with a cocktail of RTE meat microbiota consisting of Brochothrix thermosphacta, Carnobacterium maltaromaticum, Leuconostoc gelidum, and Lactobacillussakei. Products were treated at 500 MPa at 5°C for 1 or 3 min, with or without rosemary extract or nisin. Surviving cells were differentially enumerated after pressure treatment and after 4 weeks of refrigerated storage. After 4 weeks of storage, products were also analyzed by high throughput sequencing of 16S rRNA amplicons. Pressure treatment reduced counts of Listeria by 1 to 2 log (CFU/g); inactivation of RTE meat microbiota was comparable. Counts of Listeria increased by 1–3 log (CFU/g) during refrigerated storage. RTE meat microbiota did not influence pressure inactivation of Listeria but prevented growth of Listeria during refrigerated storage. Rosemary extract did not influence bacterial inactivation or growth. The combination of nisin with pressure treatment for 3 min reduced counts of Listeria and meat microbiota by >5 log (CFU/g); after 4 weeks of storage, counts were below the detection limit. In conclusion, pressure alone does not eliminate Listeria or other microbiota on RTE ham; however, the presence of non-pathogenic microbiota prevents growth of Listeria on pressure treated ham and has a decisive influence on post-pressure survival and growth.